2016
DOI: 10.1007/s12325-016-0323-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy Improves Excessive Daytime Sleepiness and Sleep Quality 6 Months Following Surgery: A Prospective Cohort Study

Abstract: IntroductionObstructive sleep apnea (OSA) is one of the most important co-morbid conditions related with morbid obesity. Bariatric procedures are associated with significant improvement in OSA. The aim of the current study was to evaluate the effect of bariatric surgery on daytime sleepiness and quality of sleep in patients that had undergone laparoscopic sleeve gastrectomy.MethodsFifty-nine patients were prospectively enrolled in the study. Pre-operative and post-operative (6 months) demographics, medical his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
(48 reference statements)
1
14
2
Order By: Relevance
“…Nearly 60% of this sample of sleeve gastrectomy patients endorsed poor sleep quality, and for this subgroup, the mean sleep duration was 5.6 hours per night, which falls below the National Sleep Foundation’s recommended 7–9 hours per night [31]. The total PSQI score in the present study ( M = 7.58) was indicative of poor sleep quality at approximately 6 months following surgery and is higher than reported in two previous studies assessing post-operative sleep quality with means of 3.0 (at 3–12 months post-operatively; [11]) and 4.6 (at 6 months post-operatively; [12]), respectively. While these studies found significant post-operative gains in sleep quality such that the mean scores indicated “good” sleep quality [11, 12], our results diverge, suggesting that sleep quality might be worse for post-operative bariatric patients with LOC eating.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Nearly 60% of this sample of sleeve gastrectomy patients endorsed poor sleep quality, and for this subgroup, the mean sleep duration was 5.6 hours per night, which falls below the National Sleep Foundation’s recommended 7–9 hours per night [31]. The total PSQI score in the present study ( M = 7.58) was indicative of poor sleep quality at approximately 6 months following surgery and is higher than reported in two previous studies assessing post-operative sleep quality with means of 3.0 (at 3–12 months post-operatively; [11]) and 4.6 (at 6 months post-operatively; [12]), respectively. While these studies found significant post-operative gains in sleep quality such that the mean scores indicated “good” sleep quality [11, 12], our results diverge, suggesting that sleep quality might be worse for post-operative bariatric patients with LOC eating.…”
Section: Discussioncontrasting
confidence: 63%
“…Recently, more attention has been directed towards examining the role of post-surgical sleep duration and quality [10, 11, 12]. For instance, average sleep duration was less in a sample of pre-operative bariatric patients ( M = 6.0 hours) compared with non-obese matched controls ( M = 7.2 hours) however, importantly, improvements in sleep duration ( M = 6.8 hours) and quality up to 12 months post-operatively were observed for the bariatric surgery group [11].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep quality improvement after bariatric surgery has been previously reported [8,18,19]. Obesity is the main risk factor for OSA, a major cause of disturbed sleep and excessive daytime sleepiness in this patient population, and previous studies confirm the effectiveness of obesity surgery for the control the OSA [19,20].…”
Section: Discussionmentioning
confidence: 66%
“…A good example of how important bariatric treatments play a role in improving the quality of life is the problem of Obstructive Sleep Apnea (OSA). Bariatric surgeries reduce the symptoms of OSA and improve sleep quality and daytime sleepiness [12]. Lack of possibility of surgical treatment results in shortened quality adjusted life years.…”
Section: Discussionmentioning
confidence: 99%